INTEGRASI DEFINISI DAN PENALARAN DALAM PROSES BERFIKIR ILMIAH - Linda Yuliandini; Suci Ulfah Suhirwah; Jenuri Jenuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Problems in the scientific thinking process often arise from unclear definitions of concepts and weak logical reasoning in drawing conclusions. Without clear definitions, concepts become obscure, while without sound reasoning, science loses its methodological footing. This article aims to explain the integration of definitions and reasoning as the basis for the formation of valid scientific knowledge. The methodology used is a literature study with a philosophical analysis approach, namely examining various literature on the philosophy of science and logic to discover the conceptual relationship between the two. The analysis is conducted by outlining the function of definitions as a conceptual foundation, reasoning as a methodological instrument, and how the integration of the two builds a logical and systematic framework for scientific thinking. The results of the study indicate that definitions play a role in defining the boundaries of a concept's meaning, while reasoning processes these concepts to produce new conclusions. The integration of the two not only prevents confusion and logical errors but also strengthens the validity of scientific knowledge. Furthermore, the application of this integration is evident in the practice of scientific research, education, and everyday decision-making. Thus, this article emphasizes that definition and reasoning are two inseparable aspects of the philosophy of science, and their integration is a prerequisite for the development of objective, systematic, and accountable knowledge.